Self-Referential Optimal Advising When Reactions are Delayed - Marco Lehmann-Waffenschmidt (Technische Universität Dresden, Fakultät Wirtschaftswissenschaften, 2006)
Like social predictions also advices addressed to the relevant agents may influence their subject and consequently may be liable to self-referentiality effects. It is a well-known phenomenon that decisionmakers tend to delay the execution of a given advice the more the less urgent the underpinning arguments appear to be to them. Particularly, this can be observed in economic and in environmental policy. What should a professional adviser do? It is the purpose of this study to provide an analytical framework in which a professional adviser's objectives are analyzed. Naturally, his first objective is to choose such an advice and such underpinning arguments that the advice really will be taken by the addressed agents (argument justification objective). This is closely related to the problem of the predictability of social events which for the first time has rigorously been analyzed by Grunberg and Modigliani in 1954. The adviser's second objective of being right with his underpinning arguments and his third objective, i.e. his potential self-interest in the ultimate outcome, will be taken into account in this study by means of a subjective utility function. This approach can be seen as complementary to the literature on strategic information transmission and credibility.
Keywords: O20; O22; 330; delayed reaction function; self-referentiality; argument justification; social reputation